Fulfillment of Children's Rights in Marriage Age Restriction in The Perspective of Mashood A. Baderin View of Human Rights (Sociological Study of Marriage Law Number 16 of 2019) - Sabbaha, Ahmad Maulana; Rahmawati, Erik Sabti (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Indonesian Government has made changes to the minimum age limit for marriage in the Marriage Law to prevent the practice of underage marriage and protect children's rights, which are part of human rights. This research aims to examine the sociological aspects of changes in the age limit for marriage in Indonesia, which basically uses the Universal Human Rights approach as the main instrument in revising the Marriage Law in Indonesia by using the view of human rights put forward by Mashood A. Baderin. This research is a normative juridical research that uses a historical and conceptual approach. The results of this research show that two sociological aspects underlie changes in the minimum age limit for marriage in Indonesia, namely the health and education aspects. Changes in the minimum age limit for marriage are intended to fight for children's rights, especially health and education. According to Mashood A. Baderin, the Al-Qur'an and Hadith have regulated children's rights. Changes in the minimum age limit for a marriage intended to fight for children's rights align with Mashood A. Baderin's views on children's rights in Islamic law.